Pengaruh Ukuran Butir Pasir Terhadap Kuat Tekan Cellular Lightweight Concrete - Putra, Sapta Amanda; Ary Wahyudie, Ilham; Darta, Yuli (Jurnal Inovasi Teknologi Terapan, 2023)
Lightweight bricks are concrete bricks that have a lighter specific gravity than concrete bricks in general. Lightweight concrete according to the Indonesian National Standard (SNI) 03-3449-2002 is concrete that has light aggregate or a mixture of light coarse aggregate and natural sand as a substitute for light fine aggregate provided that it does not exceed the maximum concrete weight of 1850 kg/m3 The size of the sand grain matters against the compressive strength of lightweight bricks. The method used in this study is using the Full Factorial method. The results of the compressive strength test showed that the average value of the largest sample was 60.90 MPa and the average value of the smallest sample was 6.70 MPa. As for the results of the density test, the largest average value was 6,135.36 kg/cm3. The results of the density test obtained the smallest average value of 2.968 kg/cm3